Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
X - Intercept
3y - 6x = 3
3(0) - 6x = 3
0 - 6x = 3
-6x = 3
-6 -6
x = -0.5
Y - Intercept
3y - 6x = 3
3y - 6(0) = 3
3y - 0 = 3
3y = 3
3 3
y = 1
X - Intercept and Y - Intercept
(x, y) = (-0.5, 1)
3y - 6x = 3
3(0) - 6x = 3
0 - 6x = 3
-6x = 3
-6 -6
x = -0.5
Y - Intercept
3y - 6x = 3
3y - 6(0) = 3
3y - 0 = 3
3y = 3
3 3
y = 1
X - Intercept and Y - Intercept
(x, y) = (-0.5, 1)
the answer is 3 times y minus six equals to 3 .y=5 so three times five is fifteen so then you take that total and subtract it with six which equals to three . hope this helps you
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.